2014
DOI: 10.1007/s10792-014-9913-0
|View full text |Cite
|
Sign up to set email alerts
|

Causes of subnormal vision in patients following cataract surgery at a tertiary hospital in Kashmir

Abstract: Cataract surgery is aimed at restoring sight to near normal vision. This study, conducted at the Department of Ophthalmology, Government Medical College, Srinagar, is an attempt to determine the causes of subnormal vision in patients following cataract surgery at a tertiary hospital in Kashmir. One hundred patients who underwent cataract surgery with an unaided visual acuity of <6/9 at 16 weeks postoperatively were included in the study. Postoperative follow-up examinations were conducted until the 16th week. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Andleeb Ahangar, Aalia Rasool Sufi et al from Kashmir (2014) reported in their SICS group that 17 (56.6 %) patients had a mean postoperative astigmatism of 0.75 ± 0.40 diopters, with the majority having against-therule (ATR) astigmatism. 20 In patients not improving with spectacle correction, posterior capsular opacity (PCO) was found in 08% of our cases. Due to the affordability of patients, we used only non square edge IOLs in all our selected cases and hence this higher percentage.…”
Section: Discussionmentioning
confidence: 71%
“…Andleeb Ahangar, Aalia Rasool Sufi et al from Kashmir (2014) reported in their SICS group that 17 (56.6 %) patients had a mean postoperative astigmatism of 0.75 ± 0.40 diopters, with the majority having against-therule (ATR) astigmatism. 20 In patients not improving with spectacle correction, posterior capsular opacity (PCO) was found in 08% of our cases. Due to the affordability of patients, we used only non square edge IOLs in all our selected cases and hence this higher percentage.…”
Section: Discussionmentioning
confidence: 71%
“…A large DD would require unscrolling followed by descemetopexy using 20% sulfur hexafluoride, 14% perfluoropropane, or suturing. [ 29 ] The reported rates of DD in MSICS vary from 0%,[ 30 ] 0.009% (3/31674),[ 7 ] 0.4% (4/1087),[ 31 ] 1.16% (8/689),[ 32 ] to 1.34% (7/522). [ 8 ]…”
Section: Perioperative Complicationsmentioning
confidence: 99%
“…Higher rates of iridodialysis were seen in MSICS in comparison to PE. [ 7 30 ] The reported rates of iridodialysis in MSICS are nil,[ 8 ] 0.03% (10/31674),[ 7 ] 0.5% (5/1087),[ 31 ] 0.73% (5/689),[ 32 ] and 6.6% (2/30). [ 30 ]…”
Section: Perioperative Complicationsmentioning
confidence: 99%
See 2 more Smart Citations